Decreased Chronic Widespread Pain on Nonworking Days Might Help Differentiate Work-Related Musculoskeletal Disorders From Fibromyalgia: A Cross-Sectional Study of Working Females - Mehmet Akif GÜLER; Mehmet Onat ÇAKIT (Archives of Rheumatology, 2020)
Objectives: This study aims to investigate whether fibromyalgia (FM) and work-related musculoskeletal disorders can be differentiated in working females by comparing their pain on nonworking and working days. Patients and methods: The study included 142 female workers (mean age 30.0±6.5 years; range, 18 to 50 years) from five different work areas: 27 factory workers, 27 janitors, 25 data automation employees, 31 nurses, and 32 physiotherapists. Demographic characteristics were recorded. FM was diagnosed according to 2016 criteria of the American College of Rheumatology. The extended version of the Nordic Musculoskeletal Questionnaire was used to evaluate the participants’ musculoskeletal complaints and the severity of their pain. Pain was assessed with visual analog scale (VAS) scores on working and nonworking days. Differences in the participants’ VAS-Pain on working and nonworking days were compared. Sensitivity, specificity, receiver operating characteristic (ROC) curve and area under the curve (AUC) were used. Results: Of the 142 working females, 32 (22.5%) were diagnosed with FM. There was a significant difference in nonworking day VAS-Pain scores between the FM patients and the work-related musculoskeletal disorder patients (p<0.001). Analysis of ROC curve for VAS-Pain difference scores yielded AUC of 0.860 (95% confidence interval=0.774–0.945) (p<0.001). ROC analysis identified 1.5 centimeters of VAS-Pain difference score as the cut-point for differentiating work-related musculoskeletal disorders and FM resulting in sensitivity of 97% and specificity of 96%. FM patients had significantly higher rates of positive answers to “visit health professionals,” “take medication,” and “sick leave” questions compared to patients with work-related musculoskeletal disorders (p<0.001). Conclusion: The amount of the decrease in pain on nonworking days may help differentiate work-related musculoskeletal disorders from FM in working females. Therefore, evaluating pain on nonworking days may help clinicians diagnose and treat FM correctly.